Non-targeted metabolomics of moldy wheat by ultra-performance liquid chromatography – quadrupole time-of-flight mass spectrometry - Gao, Boyan; Lu, Weiying; Jin, Mengchu; Chen, Yumei (Frontiers in Microbiology, 2023)
As one of the staple foods for the world’s major populations, the safety of wheat is critical in ensuring people’s wellbeing. However, mildew is one of the prevalent safety issues that threatens the quality of wheat during growth, production, and storage. Due to the complex nature of the microbial metabolites, the rapid identification of moldy wheat is challenging. In this research, identification of moldy wheat samples was studied using ultraperformance liquid chromatography - quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS) coupled with chemometrics. The non-targeted PCA model for identifying moldy wheat from normal wheat was established by using previously established compounds database of authentic wheat samples. The orthogonal projection to the latent structures-discrimination analysis (OPLS-DA) was performed. By optimizing the model parameters, correct discrimination of the moldy wheat as low as 5% (w/w) adulteration level could be achieved. Differential biomarkers unique to moldy wheat were also extracted to identify between the moldy and authentic wheat samples. The results demonstrated that the chemical information of wheat combined with the existing PCA model could efficiently discriminate between the constructed moldy wheat samples. The study offered an effective method toward screening wheat safety.